Language cognizance and sign language awareness on the part of deaf individuals at 2 nd level primary schools for hearing impaired individuals in the Czech Republic - Kučera, Pavel; Souralová, Eva (Social Welfare: Interdisciplinary Approach, 2014)
A deaf individual’s language cognizance is one of the main factors leading to his/her inclusion in the community of the deaf. Sign language has a major influence on the development and creation of deaf individuals’ identity. The conscious use of sign language as a communication tool is closely related to the different perception of the world and, thus, culture dissimilarities. At present, the subject ‘Sign Language’, contributing to the overall development of language cognizance of deaf individuals — sign language users -, is being introduced at primary schools for hearing impaired individuals within the framework education programme. The following text presents the conclusions of the research focused on ascertaining the perception of sign language, the level of knowledge relating to the theory of sign language, and the position of sign language in the society (culture of the deaf) on the part of sign language users themselves — pupils at 2nd level primary schools for hearing impaired individuals — through the qualitative approach method.
Keywords: deaf individuals; sign language; identity; language identifcation; community of the deaf